THE EFFECT OF QUALITY LEARNING MEDIA ON THE RESULTS OF LEARNING THROUGH CREATIVITY OF LEARNING IN LEARNING ONLINE TO STUDENTS IN SMA STATE 22 JAKARTA - Mayangsari, Dwi; Sudiarditha, I Ketut R.; Nurjanah, Siti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This research was conducted at SMA Negeri 22 Jakarta in East Jakarta during the pandemic with a survey method using a questionnaire as a research instrument. The data used in this study uses quantitative data using path analysis. The population in this study were all students of SMA Negeri 22 Jakarta for the 2019/2020 academic year with an affordable population of all students of class XI, totaling 324 students. The number of samples used were 72 students taken from class XI IPA 4 and 5 who attended SMA Negeri 22 Jakarta. The results of this study are as follows: (1) The quality of online learning media has a positive and significant effect on students' economic learning outcomes. (2) Learning Creativity has a positive and significant effect on students' Economic Learning Outcomes. (3) The quality of online learning media has a positive and significant effect on students' learning creativity. (4). The quality of online learning media has a positive and significant effect on learning outcomes through learning creativity as an intervention.